Sensitive and Fast Direct Conversion X‐Ray Detectors Based on Single‐Crystalline HgI2 Photoconductor and ZnO Nanowire Vacuum Diode. Issue 5 (24th February 2020) - Zhang, Zhipeng; Zhang, Zhaojun; Zheng, Wei; Wang, Kai; Chen, Huanjun; Deng, Shaozhi; Huang, Feng; Chen, Jun
Abstract: Photoconductive cold cathode X‐ray detectors are highly promising for use in medical diagnosis, industrial inspection, and scientific research applications. However, development of highly sensitive, fast, and stable direct conversion X‐ray detectors remains very challenging because of structural and material limitations. This article presents a direct conversion X‐ray detector based on a HgI2 crystal and a ZnO nanowire vacuum diode with sensitivity of 6.8 × 10 3 µCGyair −1 cm −2, which is nearly two orders of magnitude higher than that of a commercial a‐Se X‐ray detector. The X‐ray detector, which uses a high‐crystallization HgI2 photoconductor, shows a response time of 0.24 ms, thus significantly outperforming the polycrystalline HgI2 X‐ray detector. In addition, the current limitation between the HgI2 photoconductor and the ZnO nanowire cold cathodes guaranteed device reliability under high applied electric fields for practical applications. The findings presented in this work demonstrate that the proposed X‐ray detector based on the HgI2 photoconductor and the ZnO nanowire vacuum diode is highly efficient and stable. Abstract : High crystallization quality of the α‐HgI2 photoconductor is realized and the photoconductor is applied to achieve high‐sensitivity X‐ray detector. Integrating of a ZnO nanowire vacuum diode increases the operation electric field of the HgI2 photoconductor benefitting for sensitive photoresponse. Sensitive and fast direct conversion X‐ray detectors based on HgI2 photoconductor and ZnO nanowire vacuum diode are demonstrated.